Potentially Disruptive Innovations and Business Models: (How) do established SMEs respond? - Kay, Rosemarie; Nielen, Sebastian; Schröder, Christian (Senate Hall, 2019)
This study analyses how established SMEs respond to potentially disruptive innovations and business models in the course of increasing digitization. Drawing on the strategic entrepreneurship approach we argue that SMEs showing opportunity-seeking behaviour are more likely to respond to potentially disruptive innovations and business models proactively. Using a data base of 268 established SMEs in Germany, we show that established SMEs that recognize disruptive innovations and business models as a business opportunity (thereby show-ing an opportunity-seeking mindset) apply significantly more frequently strategic measures to exploit these opportunities (advantage seeking). Observing and actively evaluating relevant new technologies and developments is a key determinant of belonging to the group of SMEs demonstrating entrepreneurial, opportunity-seeking behaviour. In our sample only a minority belongs to this group of proactive established SMEs.
Keywords: SMEs|strategic entrepreneurship|digitization|disruptive innovations|new business models